“TEMOS QUE DAR CONTA DE TUDO, O TRABALHO NUNCA ACABA E NÃO TRAZ PRESTÍGIO ALGUM”: Significado do trabalho doméstico para mulheres donas de casa em Imperatriz/MA - BORRALHO, Renata Sousa (2025)
This research aims to investigate the perception of women housewives in Imperatriz about their unpaid domestic work, seeking to understand how they experience and attribute meaning to this activity within a markedly patriarchal society. We start from the hypothesis that reproductive work places women in a position of invisibility, both in the family nucleus and in the social sphere, since it remains outside of economic value. The central question that guided the investigation was: what does it mean for female housewives to dedicate themselves exclusively to domestic tasks and deal with multiple daily tasks of different levels of complexity? Based on this question, the following objectives were defined: general, (I) understand the dimensions of unpaid domestic work from the perspective of the women who perform it (general); specific, (II) analyze the role of the housewife in local society and in the Brazilian context; and (III) discuss the importance of domestic work for the economy and social life. Methodologically, a qualitative approach based on in-depth interviews was adopted (Gaskell, 2002), allowing a detailed understanding of the participants' experiences and perceptions. The research involved the collaboration of six women, aged between 34 and 66, from different social classes and socioeconomic contexts. Data analysis was based on authors such as Bruschini (1985;2006), Camarano and Pinheiro (2023), Duran (1983), Federici (2017;2019;2021), Saffioti (1976;1979), Matos and Boreli (2012), among others, with an emphasis on feminist approaches that revisit Marxian theses on productive and reproductive work. The main findings indicate that exclusive dedication to domestic work significantly restricts women's economic and professional opportunities, limiting their access to the job market and personal development, such as pursuing studies or careers. Furthermore, it became clear that domestic work, although invisible, is essential for maintaining the male workforce, ensuring that men can perform their professional activities with greater efficiency and advancement. It is concluded, therefore, that the work of housewives is a fundamental pillar for capitalist society, but remains undervalued and socially neglected.